Features earliest memories of the girls with the «emotional coldness» syndrome - Доценко, Олександра Юріївна (Psychological Counseling and Psychotherapy)
The article deals with the symthomcomplex of "emotional coldness", the inability to establishing, maintaining trusting relationships with partner and systematically manifested in the form of interpersonal dependency, countdependency and fear of intimacy. According to the analize of the earliest memories of girls it was concluded that sympthomcomplex of “emotional coldness” could started forming in early childhood as a result of family socialization.